Effect of Supplementation of Choline in Moderate and Low Crude Protein Diets on Growth Performance of Finishing Pigs from 245 to 275 lb - J. Soto; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 254 pigs (DNA 600 × 241, initially 247.4 lb) was used in a 19-d trial to determine the effects of added choline on growth performance of finishing pigs fed moderate and low CP diets. Pens of 7 or 8 pigs were allotted by BW and randomly assigned to 1 of 4 dietary treatments with 8 replications per treatment. Experimental treatments were arranged in a 2 × 2 factorial with main effects of CP (12 or 10%) and choline (none or added) to reach a final diet concentration of chloride of 823 mg/lb of diet. For overall growth performance, there was no evidence for CP × choline interaction or choline effect. Pigs fed diets with 12% CP had marginally increased (P = 0.076) ADG compared with pigs fed diets with 10% CP, which resulted in a heavier (P = 0.036) final BW. Pigs fed the diets with 12% CP also had improved (P = 0.020) F/G compared with pigs fed the 10% CP diets. In conclusion, supplementing diets with a high concentration of choline did not influence growth performance of pigs fed moderate or low CP diets.
Keywords: crude protein; choline; finishing pigs; soybean meal